THE EFFECT OF TRANSPORTATION COSTS ON FOOD PRICES OF SHOPEEFOOD AND GRABFOOD APPLICATIONS - Hurian Kamela; Ryan Saputra Alam; Abdullah Sanusi (Jurnal MEBIS (Manajemen dan Bisnis), 2022)
Ordering food using online applications is one of the technological developments. The purpose of the study was to analyze transportation costs against the food prices of Shopeefood and Grabfood applications. The research data comes from primary data (questionnaires). The total sample was 61 people, most of whom were in the Jabodetabek area for 2 months (July-August 2022). The research method is to use linear regression. The dependent variable is the Price of Food. Independent variables are Transportation Costs, Normative and Behavioral. The study’s results explained that transportation and normative costs affect the food prices of Shopeefood and Grabfood applications. This provides evidence that people's interest and desire for technological developments, especially food, is very high.